2007
DOI: 10.1111/j.1432-2277.2007.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and behavioural factors in heart transplant candidates – an overview

Abstract: Mortality among heart transplant (HTX) candidates remains high. This review of the literature shows that psychosocial characteristics like depression, social isolation and coping strategies contribute to morbidity and mortality in heart failure (HF) patients, and may also be relevant to the prognosis of HTX candidates. Based on the research to date, physical activity favourably affects subjective and objective parameters not only in HF patients, but also in HTX candidates. Depression is prevalent among HTX can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 144 publications
(215 reference statements)
2
24
0
Order By: Relevance
“…Our data suggest further that patients on VAD support experience psychosocial and emotional stress as severe as Social support by significant others has been identified as a key element for positive outcome of HTX and VAD support, and perceiving social support is one of the most positive coping strategies [11,14]. Moreover, coping by their families and significant others can influence the patients' coping in positive or negative ways [15].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our data suggest further that patients on VAD support experience psychosocial and emotional stress as severe as Social support by significant others has been identified as a key element for positive outcome of HTX and VAD support, and perceiving social support is one of the most positive coping strategies [11,14]. Moreover, coping by their families and significant others can influence the patients' coping in positive or negative ways [15].…”
Section: Discussionmentioning
confidence: 82%
“…Anxiety of not surviving the waiting period and impairments of psychosocial functioning increase with time [10]. Whereas HTX candidates benefit from physical activity [11], VAD patients are greatly limited in this regard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Overall, these findings indicate that not only medical risk but also psychosocial stress contribute to event-free survival in patients listed for cardiac transplantation, a result that is in line with the literature on psychosocial stress in heart failure. 5 Thus, not only patients entering the waiting list with high medical risk, but also those with high psychosocial stress are in utmost need of professional attention. Unfortunately, in our study, only 35% of the patients with high psychosocial stress reported that they received any psychological counseling.…”
mentioning
confidence: 99%
“…The scientific literature shows different mood disorders in both the situation prior to transplantation and thereafter; the most common that have been tested are the anxiety disorders, depression and post traumatic stress disorder (Perez San Gregorio et al, 2005;Spaderna et al, 2007) and they have been found to adversely affect the ability to accept the new organ.…”
Section: Overweightmentioning
confidence: 99%